2014
DOI: 10.1111/jdv.12458
|View full text |Cite
|
Sign up to set email alerts
|

Opportunistic toenail onychomycosis. The fungal colonization of an available nail unit space by non‐dermatophytes is produced by the trauma of the closed shoe by an asymmetric gait or other trauma. A plausible theory

Abstract: Opportunistic onychomycosis is defined, when a non-dermatophyte mould is cultured from an abnormal nail unit in the absence of a dermatophyte. The presumption is that the mould has caused the abnormal clinical appearance of the nail unit, yet there are no data available to substantiate this claim. Reports have only identified the mould being recovered from the nail unit niche. A review of the published dermatologic literature describing toenail opportunistic onychomycosis by non-dermatophyte fungi has shown to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 20 publications
1
33
0
Order By: Relevance
“…Recently, asymmetric gait nail unit syndrome (AGNUS) has been discussed as a clinically similar condition to onychomycosis, without fungal infection being present. 10,11 Patients in our study with abnormal nails in the absence of Prevalence of onychomycosis positive culture (Table 3) may be presenting with AGNUS. The prevalence of onychomycosis reported here, however, is based on mycological confirmation.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Recently, asymmetric gait nail unit syndrome (AGNUS) has been discussed as a clinically similar condition to onychomycosis, without fungal infection being present. 10,11 Patients in our study with abnormal nails in the absence of Prevalence of onychomycosis positive culture (Table 3) may be presenting with AGNUS. The prevalence of onychomycosis reported here, however, is based on mycological confirmation.…”
Section: Discussionmentioning
confidence: 76%
“…It is worth noting that clinically diagnosing DLSO or other presentations without mycological confirmation may inflate prevalence of onychomycosis. Recently, asymmetric gait nail unit syndrome (AGNUS) has been discussed as a clinically similar condition to onychomycosis, without fungal infection being present . Patients in our study with abnormal nails in the absence of positive culture (Table ) may be presenting with AGNUS.…”
Section: Discussionmentioning
confidence: 79%
“…Diabetic patients more than 50 years old are more susceptible to fungal infections in toenails due to diminished blood circulation, increased thickness of the nail plate, decreased the growth rate of the nail, and poor foot hygiene. [ 19 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 20 ] Aspergillus onychomycosis starts at the tip of the underside of the nail, where spores get accumulated, and the infection spreads toward the cuticle and the nails become thick, discolored, and flaky. [ 19 ]…”
Section: Discussionmentioning
confidence: 99%
“…It has not been fully established whether non‐dermatophyte infections occur as a primary event on healthy nails or can only affect nails already damaged by ischemia, trauma or other diseases . Recently published literature describing toenail opportunistic onychomycosis by NDMs have shown that an asymmetric gait or other trauma as well as health conditions such as diabetes and psoriasis predispose the NDMs nail colonisation.…”
Section: Introductionmentioning
confidence: 99%